Keeping Bystanders Active: Resuscitating Resuscitation Skills - Maaß, Sarah C.; Sense, Florian; Gluck, Kevin A.; van Rijn, Hedderik (Frontiers in Public Health, 2019)
Objective. Sufficient CPR skills in the general population are essential to make them active bystanders and contribute to an effective rescue chain in cardiac arrest emergencies. However, having a large proportion of the population be regularly retrained is practically infeasible. The aim of this study was to assess and retrain cardiopulmonary resuscitation (CPR) skills of individuals who received (limited) CPR training several months to years prior. Method. 99 German adults in a possession of a driver's license were asked to perform CPR on a Laerdal Resusci Anne® QCPR manikin (Laerdal, Stavanger, Norway). After initial assessment, participants watched an instructional video and completed short, isolated compression and ventilation practice with live feedback. CPR proficiency was assessed again after retraining and after a retention interval of 45 minutes. Results. Our results indicate that only 2% of participants managed to reach the performance criterion set by the European Resuscitation Council Guidelines, with most failing to reach even the lowest levels of performance. This corroborates earlier observations that CPR skills have deteriorated almost completely after a long retention interval, calling into question “one-and-done” certification of this basic life-saving. However, we also demonstrate that performance strikingly increased after watching a 6-minute instructional video and a short opportunity for isolated practice. This increase in performance was stable over 45 minutes with 96% of participants meeting criterion performance Closer inspection of the isolated compression practice data suggests that performance was very high at the start of the practice already, indicating that short refresher videos might suffice to change bystanders that would not have initiated CPR due to lack of knowledge into active first responders. Conclusion. We suggest that short refresher trainings could be an effective and affordable means of improving basic lifesaving skills to increase the effective contribution of bystanders during emergencies.